Prospects for the production of culinary products from turkey meat (a review) - Z. N. Khatko; A. S. Shirokova (Новые технологии, 2022)
The purpose of the research is to analyze the prospects for the production and processing of turkey meat to expand the range of culinary products. The technological potential of turkey meat for the production of culinary products has been considered. High biological value and dietary qualities have been noted. The turkey is considered to occupy a significant segment in the volume of poultry production, which is constantly increasing as a result of the growth in consumer demand. The volumes of production of turkey meat have been given and the largest domestic producers of turkey meat noted. The dynamics of production and consumption of turkey meat in Russia has been presented. The structure of consumption of turkey meat in Russia in % of the total amount of meat consumed has been given. The types of turkeys and their characteristics have been considered. The advantages of choosing turkey meat in comparison with other types of poultry meat are noted. According to its biological and economic characteristics, turkey meat is one of the most promising types. The range of culinary products from turkey meat, its chemical composition, fabrics, varieties have been considered. The industrial advantages of white meat compared to red meat have been shown. An assortment of appetizers, first and second courses is given. Data analysis shows that minimally processed turkey is an excellent source of protein, vitamins and minerals. Turkey meat is regarded to be the meat of the future due to its low fat content and high protein content. Turkey meat, due to its high technological potential, the absence of an allergic effect on the human body, is the primary raw material for the production of culinary products for baby food, dietary, therapeutic, preventive, functional purposes. To prepare new types of culinary products from turkey meat and expand the range of this group, it is advisable to use innovative sous-vide technology that preserves the maximum nutritional and biological value of the finished product.